Targeting small-scale irrigation investments using agent-based modeling: Case studies in Mali and Niger - Olayide, Olawale E.; Sangare, Saadatou A.; Koo, Jawoo; Xie, Hua (University of Bonn, 2020)
Small-scale irrigation has been identified as a potential adaptation strategy for climate change and boosting food security and livelihoods in dry regions. This study presents the analysis of the potential adoption of small-scale irrigation in two West African countries (Mali and Niger) by using a spatially explicit analytical framework. It underscores the need for strategically investing in the management of ground and surface water resources for the development of small-scale irrigation systems in the two countries. The study implemented an agent-based modeling technique to simulate small-scale irrigation decisions at the district and national level. The results revealed that, while small-scale irrigation can increase crop productivity in both countries, its adoption may be constrained by water scarcity and tensions in water allocation. Strategic water resource development plans should be established to ensure efficient and sustainable irrigation schemes, especially for areas with high potential profitability.